DIAGNOSTIC PERFORMANCE OF PROSTATE HEALTH INDEX (PHI) IN PREDICTING PROSTATE CANCER ON PROSTATE BIOPSY; A SINGLE CENTER STUDY - Krstev, Toni; Stojanoski, Ivica; Ilievski, Lazar; Tufekchioski, Nerhim; Stojcheva-Taneva, Olivera; Trojacanec, Jasmina; Ilijevska, Cvetanka Volkanovska (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
The Prostate Health Index (PHI) is a new test combining total, free and (-2)proPSA into a single score. It was recently approved by the FDA and is now commercially available in the U.S., Europe and Australia. Our aim is to investigate whether PHI improves specificity for detecting clinically significant prostate cancer and can help to reduce prostate cancer biopsies. We examined 100 men age 50 years or older with prostate specific antigen 4 to 10 ng/ml („gray zone„) and normal digital rectal examination with suspected prostate cancer who had undergone biopsies and were divided into a benign and malignant group.  In this population we compared the performance of prostate specific antigen, % free prostate specific antigen, (-2)proPSA and PHI to predict biopsy results and, specifically, the presence of clinically significant prostate cancer using multiple criteria. We found statistically significantly increased levels of −2proPSA, PHI and PSA and decreased levels of %freePSA in patients diagnosed with prostate cancer by prostate biopsy vs. patients with benign prostatic conditions (median values: −2proPSA: 28.3 vs. 20.11 ng/l, PHI: 73.04 vs. 30.5, total PSA: 7.3 vs. 6.48 ng/ml and %free PSA: 17.06 vs. 25.62%). On receiver operating characteristic analysis PHI had the highest AUC for overall prostate cancer (AUCs PHI 0.954, percent free prostate specific antigen 0.345, (-2)proPSA 0.753 and prostate specific antigen 0.656). The optimal cut-off for PHI in the study population was 42.8 with sensitivity of 85.7% (95% CI: 54.8-90.6) and specificity of 86.1% (CI 95%, 0.913-0.995). Whereas, in the tPSA for cut-off 6.54 sensitivity is 61.9 and specificity 59.5, respectively.  The Prostate Health Index was significantly higher in men with Gleason 7 or greater. In our study for the PHI levels (36-54.99) only 23.08% of patients had Gleason score ≥ 7.In patients with  PHI levels >55, 76.92% of patients had Gleason score ≥ 7. The new PHI test outperforms its individual components of total, free and (-2)proPSA for the identification of clinically significant prostate cancer. PHI may be useful as part of a multivariable approach to reduce prostate biopsies and overdiagnosis. Keywords:   PHI; prostate cancer, early detection, prostate biopsy.